2002
DOI: 10.1085/jgp.20028639
|View full text |Cite
|
Sign up to set email alerts
|

Control of Outer Vestibule Dynamics and Current Magnitude in the Kv2.1 Potassium Channel

Abstract: In Kv2.1 potassium channels, changes in external [K+] modulate current magnitude as a result of a K+-dependent interconversion between two outer vestibule conformations. Previous evidence indicated that outer vestibule conformation (and thus current magnitude) is regulated by the occupancy of a selectivity filter binding site by K+. In this paper, we used the change in current magnitude as an assay to study how the interconversion between outer vestibule conformations is controlled. With 100 mM internal K+, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 27 publications
3
29
0
Order By: Relevance
“…The most favorable conformation now involves an H-bond between the side chains of E80 and C81 occupancy of the sites in the filter and inducing conformational changes in the external vestibule through an inter-subunit H-bond network. These data add further support for the idea that the external vestibule and selectivity filter are dynamic structures [18,33,38,57,75] critically involved in many aspects of channel function. Fig.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The most favorable conformation now involves an H-bond between the side chains of E80 and C81 occupancy of the sites in the filter and inducing conformational changes in the external vestibule through an inter-subunit H-bond network. These data add further support for the idea that the external vestibule and selectivity filter are dynamic structures [18,33,38,57,75] critically involved in many aspects of channel function. Fig.…”
Section: Discussionsupporting
confidence: 69%
“…D378 in Kv2.1 may be involved in some of these phenomena. External K + ions can induce conformational rearrangements of the external vestibule in Kv2.1 that affect TEA binding [33] and K + current magnitude [38], and these effects have been suggested to be mediated by a low-affinity, external K + -binding site associated with the selectivity filter [68]. C-type inactivation [25,28,69] has been shown to be antagonized by external K + ions [70].…”
Section: External K + Ions Alter Single-channel Gatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, its inhibition of I K might result from open channel block. It also remains to be determined to what extent this compound may have a higher affinity for the open conformation of K + channels than for the closed conformation without evoking open channel block, because the outer vestibule of the Kv2.1 channel might interconvert between the two conformations (Andalib et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Kv2.1 mRNA in heart could be altered under certain pathological conditions associated with arrhythmia (Xu et al, 1999;Zhou et al, 2003;Huang et al, 2000). Moreover, the Kv2.1-encoded K + channels could be important under conditions of high frequency firing of neurons (Klemic et al, 1998;Du et al, 2000;Andalib et al, 2002), and have been found to be linked to a mechanism through which the apoptotic signaling cascade occurs in cortical neurons (Pal et al, 2003) and in H9c2 cells (Ekhterae et al, 2003). This cell line is thus thought to be a useful model with which to study the biophysical and pharmacological properties of Kv2.1 channel.…”
Section: Introductionmentioning
confidence: 99%